(untitled) (Scientia Agricola, 2006)
The knowledge of the digestive system of bullfrogs is an important step for the determination of their nutritional requirements throughout growth phases. With the objective of evaluating the enzymatic activity of lipase in the intestinal content of bullfrogs (Rana catesbeiana Shaw, 1802), 100 animals with median weight of 3.6 g were distributed in stalls under controlled temperature and photoperiod. The frogs, selected at the post-metamorphic phase, received commercial extruded diet ad libitum throughout the 87-day experiment. The collections of the intestinal content were performed by the desensitization of the frogs in ice and water at 0ºC and subsequent isolation of the small intestine. Determination of lipase activity was performed with a commercial enzymatic kit (Lipase-Bioclin, MG, Brazil), first measured in samples taken at day three (3.46 UI). During the initial phase the bullfrog possesses low lipase hydrolysis capacity was found, having a specific activity of 217 UI mg-1. In the subsequent period both lipase activity and specific lipase activity continuously increased. Lipase activity as a function of bullfrog weight fell after day twenty and reached 0.33 UI g-1, for frogs of medium weight (179 g). Feed for bullfrogs at the post-metamorphic phase weighing more than 10 g can have larger amounts of ingredients containg lipids, due to the increased digestive capacity of these frogs.